2022
DOI: 10.2147/idr.s353858
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Genotype and Correlation of Clinical Severeness with Presence of the Type VI Secretion System in Klebsiella pneumoniae Isolates Causing Bloodstream Infections

Abstract: Background Klebsiella pneumoniae ( K. pneumoniae ) causes bloodstream infection (BSI), which is responsible for a high rate of morbidity and mortality among different populations. In mainland China, data on the correlation and features of the type VI secretion system (T6SS) gene cluster in K. pneumoniae is currently scarce. As a result, we conducted a prospective investigation to determine the involvement of the T6SS in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
4
3
0
Order By: Relevance
“…We identified hvKp in 41.42% (70/169) of patients and hypermucoviscosity phenotype in 47.93% (81/169). Moreover, the results indicated that there were more hvKp strains among T6SS-positive strains than among T6SS-negative strains ( p < 0.001), which was similar to the findings of a study by Yin et al ( Zhang et al, 2022 ). The most prevalent hvKp isolates were ST23 (36/70), and ST23 in T6SS-positive isolates was significantly higher than in the T6SS-negative isolates.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We identified hvKp in 41.42% (70/169) of patients and hypermucoviscosity phenotype in 47.93% (81/169). Moreover, the results indicated that there were more hvKp strains among T6SS-positive strains than among T6SS-negative strains ( p < 0.001), which was similar to the findings of a study by Yin et al ( Zhang et al, 2022 ). The most prevalent hvKp isolates were ST23 (36/70), and ST23 in T6SS-positive isolates was significantly higher than in the T6SS-negative isolates.…”
Section: Discussionsupporting
confidence: 90%
“…Positive results for hcp , icmF , and vgrG genes confirmed T6SS positivity ( Zhou et al, 2020 ; Liao et al, 2022 ; Zhang et al, 2022 ), and 36.1% (61/169) of our strains were T6SS-positive; this was much higher than the rate in blood stream infection (BSI) (20.1%) ( Zhou et al, 2020 ). We identified hvKp in 41.42% (70/169) of patients and hypermucoviscosity phenotype in 47.93% (81/169).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Escherichia coli ATCC25922 and K. pneumoniae ATCC700603 were used as quality controls as previously described. 26 …”
Section: Methodsmentioning
confidence: 99%